The Structural Integrity And Fracture Behaviour Of Teeth Restored With Peek And Lithium-disilicate Glass Ceramic Crowns - Sami Aldhuwayhi; Muhammad Syafiq Alauddin; Nicolas Martin (MDPI, 2024)
Indexed by WOS/Scopus/ERA